The rise of congenital syphilis in Canada: threats and opportunities - Ashorkor Tetteh; Victoria Moore (Frontiers in Public Health, 2025)
IntroductionIn Canada, rates of congenital syphilis have been increasing rapidly in recent years, following a surge in infectious syphilis. These trends call for a closer look at missed opportunities for testing, diagnosis, treatment, and follow-up of pregnant individuals. The epidemiological situation is especially serious given that effective treatment is available for syphilis during pregnancy and that congenital syphilis is a preventable outcome that engenders adverse birth outcomes such as miscarriage, stillbirth, and neonatal death as well as potentially lifelong ocular, neurological, hepatosplenic, and musculoskeletal sequelae. The objective of this study is to examine the factors associated with congenital syphilis trends and to highlight promising initiatives and programs across the country committed to addressing these trends.MethodsA literature review with a focus on Canadian studies was conducted to identify factors that may be driving the continued increase in early congenital syphilis rates over the past decade. An environmental scan of initiatives and programs providing syphilis care and support was also conducted.ResultsKey factors identified in association with congenital syphilis outcomes included a lack of timely and repeated prenatal syphilis screening, inadequate prenatal treatment and follow-up of syphilis infection, barriers to accessing prenatal care caused by multiple intersecting social determinants of health as well as by certain structural determinants of health, and substance use. A number of initiatives to improve syphilis care within the health care system and several community-based programs filling in some of the gaps in syphilis care and support are making important advances in addressing the epidemiological situation with syphilis.DiscussionMuch work is underway at various levels of government and local community to address the situation. Key recommendations for maximizing impact in curbing infectious and congenital syphilis rates include the following: planning an integrated strategy for addressing sexually transmitted and blood-borne infections as a whole; adopting a more holistic approach to improving health and wellbeing; developing targeted interventions for addressing structural and social barriers to health equity; and taking a collaborative approach to response by involving multilevel stakeholders, such as key populations, community groups, health care providers, and public health authorities.